A line in the dark - Lo, Malinda (Dutton Books, 2017)
"When Chinese American teenager Jess Wong's best friend Angie falls in love with a girl from the nearby boarding school, Jess expects heartbreak. But when everybody's secrets start to be revealed, the stakes quickly elevate from love or loneliness to lifeor death"--